Carcass quality, evaluation and classification of the main species of zootechnical interest: bovine, swine and poultry (Research, Society and Development, 2020)
The production chains of animal proteins have evolved and adapted to niches of offers and demands on the world stage. The prerogatives of meat production and processing demanded, over time, animal welfare standards, good manufacturing practices, classification and typification of carcasses. Each species adjusts with respect to these pre and production protocols, with their bottlenecks and adjustments, as well as their procedures that change when assessing carcass quality and typification. The intention goes beyond meeting various types of regulations throughout the world, as well as consumer demands and market requirements. When it comes to the main animal proteins consumed, pork, beef and poultry, several main niches are evaluated: the Brazilian niche for domestic consumption and the different export niches. Based on this, the objective was to review the rules of pre-production, production, animal welfare guidelines as well as classification and classification of the carcass of swine, bovine and poultry species.